2009
DOI: 10.1074/jbc.m109.037846
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Phosphatidylinositol Mannosides Negatively Regulate Host Toll-like Receptor 4, MyD88-dependent Proinflammatory Cytokines, and TRIF-dependent Co-stimulatory Molecule Expression

Abstract: Mycobacterium tuberculosis modulates host immune responses through proteins and complex glycolipids. Here, we report that the glycosylphosphatidylinositol anchor phosphatidyl-myo-inositol hexamannosides PIM 6 or PIM 2 exert potent anti-inflammatory activities. PIM strongly inhibited the Tolllike receptor (TLR4) and myeloid differentiation protein 88 (MyD88)-mediated release of NO, cytokines, and chemokines, including tumor necrosis factor (TNF), interleukin 12 (IL-12) p40, IL-6, keratinocyte-derived chemokine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 57 publications
5
85
0
Order By: Relevance
“…LAM mediates entry in to macrophages via the mannose receptor aiding the bacilli in avoiding phagosome-lysosome fusion, oxidative burst and altered calcium and cytokine responses (3,23,42,43,48). LAM has also been shown to bind to Toll-like receptors and induce signaling events important in the host response in tuberculosis (15,16). Thus, LAM is generally considered to be a crucial factor in mycobacterial pathogenesis.…”
mentioning
confidence: 99%
“…LAM mediates entry in to macrophages via the mannose receptor aiding the bacilli in avoiding phagosome-lysosome fusion, oxidative burst and altered calcium and cytokine responses (3,23,42,43,48). LAM has also been shown to bind to Toll-like receptors and induce signaling events important in the host response in tuberculosis (15,16). Thus, LAM is generally considered to be a crucial factor in mycobacterial pathogenesis.…”
mentioning
confidence: 99%
“…founding to several studies where PIM 2 was found to be proinflammatory in its function (10,12), several members of PIM family that are TLR2 agonists are majorly anti-inflammatory in nature and can suppress pro-inflammatory responses mediated by other PRRs (13)(14)(15). We sought to analyze the cross-regulation, if any, between PIM-induced TLR2 signaling and another PRR signaling like NOD2 pathway.…”
Section: Ac 2 Pim Inflects Nod2-induced Immunomodulators-con-mentioning
confidence: 99%
“…Functional consequences of PIM-induced TLR2 signaling span both pro-and anti-inflammatory capacities (10,(12)(13)(14)(15). Importantly, stimulation of PIM-TLR2 pathway down-regulates TLR4-induced pro-inflammatory signals (13).…”
mentioning
confidence: 99%
“…Mycobacterial lipids have long been implicated in the induction of responses in both the innate and adaptive cell-mediated immune responses (17)(18)(19)(20)(21). Although one strategy has been published which allows the isolation of PIMs from the avirulent M. bovis BCG strain (18,(22)(23)(24) and M. tuberculosis H37Rv (22) and certain synthetic molecules (17,19,21), in this study we successfully developed a novel method for extracting and subsequently highly purifying and characterizing individual PIM species from the polar fraction of virulent M. tuberculosis H37Rv.…”
Section: Discussionmentioning
confidence: 99%
“…Although one strategy has been published which allows the isolation of PIMs from the avirulent M. bovis BCG strain (18,(22)(23)(24) and M. tuberculosis H37Rv (22) and certain synthetic molecules (17,19,21), in this study we successfully developed a novel method for extracting and subsequently highly purifying and characterizing individual PIM species from the polar fraction of virulent M. tuberculosis H37Rv. The method developed here improves upon the previously published protocols primarily by using a French press to disrupt the bacterial cells, thereby increasing PIM yield.…”
Section: Discussionmentioning
confidence: 99%